Analysis of the Effect of User Satisfaction on the Quality of the Shopee Application with the End User Computing Satisfaction Method (Survey on Followers of the Shopee Indonesia Instagram Account) - Baldhan Difa; Agung Triayudi; Endah Tri Esti Handayani (SaNa: Journal of Blockchain, NFTs and Metaverse Technology, 2024)
Shopee is one of the e-commerce platforms in Indonesia that supports the marketplace business model. Shopee faces a big challenge to compete with a large number of other e-commerce because it is one of the marketplaces that enliven the mobile segment. To win the competition, marketplace organizers must be able to meet consumer needs to win the competition because the rapid and diverse growth of e-commerce results in increasingly fierce competition. A service can be said to be successful in providing satisfaction if it can meet the needs of its users, and user satisfaction itself can be interpreted as an important thing for every service provider. User satisfaction with services can be used to identify the good and bad sides of services that can be implemented so that user needs can be met. In this study, the End User Computer Satisfaction (EUCS) method is used, the EUCS method has 5 variables that can be used in the analysis process, namely the Content, Accuracy, Format, Ease of Use, and Timeliness variables. The research was conducted by distributing questionnaires to @shopee_id Instagram followers, from distributing questionnaires, 385 data were taken as samples to measure Shopee marketplace user satisfaction. The results of the presentation of Shopee marketplace user satisfaction on all variables are stated to have a very satisfactory data interpretation because the presentation value is above 81%